홍수터여과에서 집수관의 최적설계 연구 - 피성민(Seong Min Pi); 김승현(Seung Hyun Kim) (Daehan hwan'gyeong gonghag hoeji, 2012)
In order to obtain information on the design parameters of the horizontal laterals in floodplain filtration, laboratory-scale sand-box experiments were performed where the head distributions on the laterals and the groundwater profiles were measured according to the change in parameters including lateral diameter, hydraulic conductivity of the sand, water level at the well and raw-water supply rate. Measured data were analyzed using a numerical code in order to identify the discharge intensity distribution along the laterals. It was observed from the result that the lowering of the water level at the well had minimal adverse effect on the performance of the floodplain filtration. Results also elucidated that the low conveyance of the laterals to transmit the filtrate was compensated and supplemented by a natural augmentation in horizontal conveyance through the aquifer when the raw-water supply rate exceeded the adequate recovery rate. With this mechanism, the water quality is expected to improve further since the travel distance through the aquifer is amplified. Based on these findings it can be suggested that the diameter of the lateral used in the floodplain filtration may be smaller than those in riverbank/bed filtration. It was also found that the ratio between the head loss occurring in a lateral and the total head loss in the floodplain filtration was proportional to the exit velocities of the laterals, which may be used to design and/or evaluate the lateral in floodplain filtration. 홍수터여과에서 집수관의 설계에 대한 자료를 얻기 위해 실험실 규모의 모래통 실험을 수행하였으며, 집수관의 직경, 모래의 투수계수, 집수정의 수위 그리고 지표에서의 원수공급률 등의 변화에 따른 집수관에서의 수두분포와 지하수면 분포를 측정하였다. 측정결과를 수치해석코드에 적용하여 집수관 각 부위에서의 여과수 유입률도 파악하였다. 이들 자료로부터 홍수터여과에서 집수정의 운영수위를 낮춤으로 인한 부작용은 없을 것으로 예상되었으며, 적절한 회수능력에 비해 원수공급률이 큰 경우 대수층에서의 수평방향의 흐름이 발달하여 수평집수관의 통수능 부족을 보완함을 알 수 있었다. 이 경우 여과수의 토양중 이동거리가 늘어나므로 여과수의 수질개선에도 도움이 될 것으로 판단되었고, 따라서 홍수터여과에서는 강변/하상여과에서보다 더 작은 직경의 수평집수관을 사용할 수 있음을 알 수 있었다. 전체 수두손실중 수평집수관에서의 수두손실이 차지하는 비율이 수평집수관 출구유속과 비례함을 알 수 있었으며, 이를 이용하면 홍수터여과에서 수평집수관의 설계와 평가가 가능할 것으로 판단되었다.